The COVID-19 Disappeared: From Traumatic to Ambiguous Loss and the Role of the Internet for the Bereaved in Italy - Testoni, Ines; Azzola, Claudia; Tribbia, Noemi; Biancalani, Gianmarco; Iacona, Erika; Orkibi, Hod; Azoulay, Bracha (Frontiers in Psychiatry, 2021)
In Italy, in the very first phase of the COVID-19 pandemic there was a dramatic rise in mortality. However, families were forbidden because of lockdown regulations to be with their loved ones at their deathbeds or to hold funerals. This qualitative study examined bereavement experiences among family members, how they processed their grief, and how they used social networks in particular by uploading photographs during the working-through of bereavement. The sample was composed of 40 individuals aged 23-63 (80% women) from different Italian cities severely impacted by the virus, including a subgroup from the province of Bergamo, which was the city with the highest mortality rate during that time. All interviews were conducted by phone, Skype, or Zoom. Then, the transcriptions underwent a thematic analysis using Atlas.ti. The main themes that emerged were: abandonment anger and guilt, dehumanized desaparecidos, derealization and constant rumination, and social support and the importance of sharing photos on Facebook. Importantly, the use of social networks proved to be a valuable source of support and photographs were a powerful tool in facilitating the process of mourning by encouraging narration and sharing. Grief had a complex profile: on the one hand, it was traumatic and characterized by all the risk factors causing mourners to experience prolonged grief, but on the other, some features were similar to ambiguous loss (that occurs without closure and clear understanding) because of the impossibility to be with their relatives in their final moments. The possible relationships between ambiguous loss, the use of internet, and the risk of prolonged grief are discussed.